High-priced and dangerous: Nuclear power is not an option for the climate-friendly energy mix - Ben Wealer; Simon Bauer; Leonard Göke; Christian R. von Hirschhausen; Claudia Kemfert (DIW Weekly Report, 2019)
The debate on effective climate protection is heating up in Germany and the rest of the world. Nuclear energy is being touted as 'clean' energy. Given the circumstances, the present study analyzed the historical, current, and future costs and risks of nuclear energy. The findings show that nuclear energy can by no means be called 'clean' due to radioactive emissions, which will endanger humans and the natural environment for over one million years. And it harbors the high risk of proliferation. An empirical survey of the 674 nuclear power plants that have ever been built showed that private economic motives never played a role. Instead military interests have always been the driving force behind their construction. Even ignoring the expense of dismantling nuclear power plants and the long-term storage of nuclear waste, private economy-only investment in nuclear power plant would result in high losses- an average of five billion euros per nuclear power plant, as one financial simulation revealed. In countries such as China and Russia, where nuclear power plants are still being built, private investment does not play a role either. Nuclear power is too expensive and dangerous; therefore it should not be part of the climate-friendly energy mix of the future.
Keywords: L51; L95; Q48; 330; nuclear power; net present value; profitability; economic history